Psychology themes and variations - Weiten, Wayne 1950- (Pacific Groove, California Brooks/Cole Publishing Company, 1989)
The aim of this text is to educate students about psychology and to leave them with lasting impressions of the discipline as well as its subject matter.
1. The evolution of psychology -- 2. The research enterprise in psychology -- 3. The biological bases of behavior -- 4. Sensation and perception -- 5. Variations in consciousness -- 6. Learning through conditioning -- 7. Human memory -- 8. Language and thought -- 9. Intelligence and psychological testing -- 10. Motivation and emotion -- 11. Human development across the life span -- 12. Personality: theory and research -- 13. Stress, coping, and health -- 14. Psychological disorders -- 15. Psychotherapy -- 16. Social behavior.
Includes bibliographical references (pages 655-677) and indexes.
Keywords: Psychology